Kedudukan Akun Media Sosial Sebagai Warisan Digital Dalam Perspektif Hukum Perdata di Indonesia - Devi Yulida; Anak Agung Gede Ananta Wijaya Sahadewa; Xavier Nugraha (Kertha Wicaksana, 2024)
Globalization, accompanied by advancements in science and technology, has increased the usage of social media in Indonesia. Currently, social media accounts serve not only as platforms for interaction but also as potential sources of significant economic value. Moreover, regulations concerning the inheritance of social media accounts remain unclear and vary across platforms. The research methodology employed utilizes the normative juridical method, incorporating conceptual and case approaches. This study involves analysis of laws, court decisions, and social media platform policies. The research findings indicate that an extensive interpretation of inheritance in civil law, by considering their economic value, encompasses social media accounts. However, the implementation of social media account inheritance encounters various obstacles, including inconsistent platform policies. Some platforms have facilitated account preservation as memorials, but clarity regarding access to content or account management is lacking. Concerns persist regarding legal protection for heirs concerning social media accounts as inheritance. In the context of Civil Law, clear legal protection is necessary to ensure that heirs' rights are fulfilled, especially in acquiring economic benefits from inherited social media accounts. Furthermore, this paper underscores the necessity for clearer regulations within Civil Law concerning the inheritance of social media accounts. Strong legal protection is required to ensure justice for heirs and facilitate the effective and efficient resolution of digital legacy.